Army of darkness [videorecording (Blu-Ray)] - Raimi, Sam; Raimi, Ivan, 1956-; Campbell, Bruce, 1958-; Davidtz, Embeth, 1966-; Gilbert, Marcus, 1958-; LoDuca, Joseph (Shout! Factory, 2015)
Ash, the handsome shotgun-toting, chainsaw-armed department store clerk, is time warped by Demonic forces, into the Dark Ages, where he romances a beauty and faces legions of the undead. Can he save the living, rescue his girlfriend, and get back to his own time?